Conquering Digital Marketing: Powerful Strategies for Accelerating Business Growth - Siddiqueee, Md. Shahadat Hossain; Ali, Md. Mokshud (International Journal of Business and Economics, 2024)
Understanding digital marketing tactics is now crucial for company expansion in the digital age due to the quickly changing technology landscape. This study investigates the efficacy of modern digital marketing strategies with an emphasis on how they support significant company growth. This study is significant because it offers practical advice on how to use data analytics, customization, and cutting-edge technology like machine learning and artificial intelligence to maximize digital marketing initiatives. The main goal of this study is to determine and evaluate the best digital marketing tactics that spur company expansion. Using a thorough literature review methodology, the study assesses the effects of different digital marketing methods on business performance by looking through contemporary academic sources. Important results show that cross-channel and multi-channel marketing techniques greatly improve brand coherence and consumer engagement. Enhancing targeting accuracy and campaign efficacy requires the use of data analytics and artificial intelligence capabilities. While ethical principles and digital transformation are essential for maintaining consumer trust and competitive advantage, personalization and customer feedback integration play a critical role in driving engagement and conversion rates. Furthermore, social media, influencer marketing, and strong content tactics work well to increase brand awareness and adherence. Strategic agility is ensured by remaining up to date with emerging trends, and marketing outcomes are further enhanced through optimization of conversion rates and user experience design. These findings' implications imply that companies should take a multifaceted strategy to digital marketing, including cutting-edge technologies and emphasizing ethical and personalized practices. It is advised to use multi-channel marketing techniques, make use of AI and data analytics, prioritize ethical marketing, and continuously improve user experience and content. Future studies ought to investigate how new digital trends—like gamification and behavioral targeting—affect the efficiency of marketing campaigns and the expansion of companies. In addition to offering a foundation for companies hoping to succeed in the cutthroat digital economy, this research advances our understanding of successful digital marketing tactics.